Sialarrhea in pregnant women - Ashjei, SHD (Iran University of Medical Sciences, 1995)
Some of the pregnant women have sialarrhea and they are suffering from this phenomenon and are very irritable persons. In this paper, we are introducing some of the reasons of this disease and discussing about women who suffering from this disease. Also, we are proposing some nursing interventions about it. There is need for further nursing researches for nurses to better understand this problem. Many physical problems often occur in pregnancy and most of them are tolerable and short time but in some women there are long-term inconveniences, like nausea and sialarrhea. Sialarrhea has unknown resource and has sudden onset. There are very much and invariable saliva secretion in these women (more than 1900 ml/day).